2017
DOI: 10.1016/j.mce.2016.07.036
|View full text |Cite
|
Sign up to set email alerts
|

A brief history of the search for the protein(s) involved in the acute regulation of steroidogenesis

Abstract: The synthesis of steroid hormones occurs in specific cells and tissues in the body in response to trophic hormones and other signals. In order to synthesize steroids de novo, cholesterol, the precursor of all steroid hormones, must be mobilized from cellular stores to the inner mitochondrial membrane (IMM) to be converted into the first steroid formed, pregnenolone. This delivery of cholesterol to the IMM is the rate-limiting step in this process, and has long been known to require the rapid synthesis of a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 149 publications
(176 reference statements)
1
31
0
1
Order By: Relevance
“…2008). These observations, and the localization of STAR at the outer mitochondrial membrane, suggest a critical role for STAR in cholesterol translocation (Clark 2016, Stocco et al . 2017).…”
Section: Effects Of Aging On Steroidogenesismentioning
confidence: 98%
“…2008). These observations, and the localization of STAR at the outer mitochondrial membrane, suggest a critical role for STAR in cholesterol translocation (Clark 2016, Stocco et al . 2017).…”
Section: Effects Of Aging On Steroidogenesismentioning
confidence: 98%
“…Furthermore, mitochondrial-related proteins such as adenine nucleotide transporter (ANT) at inner mitochondrial membrane (IMM) and voltage-dependent anion channel (VDAC) at OMM have also been found in MAM, supporting the idea that cholesterol could move from ER to mitochondria via a TSPO/VDAC/STARD1/ANT-dependent mechanism (Figure 3 ). This is based on observations indicating an interaction between ANT, VDAC, and TSPO (Allouche et al, 2012 ; Vance, 2014 ; Stocco et al, 2017 ), and the fact that STARD1 is first loaded onto the MAM to interact with VDAC2 for its processing to mature active form at the OMM (Prasad et al, 2015 ). However, the role of TSPO in mitochondrial cholesterol trafficking is under debate.…”
Section: Cholesterol Metabolism In the Cnsmentioning
confidence: 99%
“…However, cholesterol must reach at IMM for the synthesis of neurosteroids in the brain, which are necessary for normal stimulation of GABAergic currents, Purkinje cells's response modulation to excitatory amino acids and the enhancement of memory function (Stocco et al, 2017 ). StAR-dependent delivery of cholesterol from the OMM to the IMM governed by STARD1 is the rate-limiting step for steroidogenesis by facilitating generation of pregnenolone (precursor of all steroids) from cholesterol through metabolism by cytochrome p450scc (CYP11A1, Figure 3 ; Elustondo et al, 2017 ; Stocco et al, 2017 ). In steroidogenic cells (including specialized neurons), the very low IMM-cholesterol levels enable a faster modulation of steroidogenesis by the rate of the OMM-to-IMM transport of cholesterol rather than enzymatic activity-dependent pathways.…”
Section: Cholesterol Metabolism In the Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevailing model at that time was that de novo synthesis of a protein factor upon hormonal stimulation was necessary for the cholesterol transfer. Furthermore, this factor needed to fulfill the following criteria: be newly synthesized upon hormonal stimulation in a time- and dose-dependent manner, be localized at the mitochondria, and have a short-half (reviewed in Clark and Stocco, 2014; Stocco et al, 2016). Here, I will highlight the studies which demonstrated that the St eroidogenic A cute R egulatory protein (StAR) fulfills the criteria for the acute regulator of steroidogenesis.…”
Section: Star (Stard1) Discovery and Functionmentioning
confidence: 99%